Spatiotemporal mechanism of urban heat island effects on human health—Evidence from Tianjin city of China - Dai, Yifang; Liu, Tongtong (Frontiers in Ecology and Evolution, 2022)
The increasingly intensifying global warming and urban heat island (UHIs) are seriously damaging the physical and mental health of urban residents. However, the spatiotemporal evolution of how high temperatures affect human health in megacities remains unclear. Therefore, in this study, with Tianjin during 2006–2020 as an example, and based on data from meteorological stations, Landsat remote sensing images, and point of interest big data, this study applied hot- and cold-spot statistics and remote sensing retrieval in numerical modeling and established an appraisal system to assess how and to what extent UHIs affect resident health. The results showed that the overall influence of UHIs on respiratory and cardiovascular diseases and mental health increased to 373 km2 in area and two levels in intensity; the influence was mainly concentrated in the downtown area, with a rising influence level. Owing to the dual-core structure of the city, the influence was distributed along the main traffic lines in Binhai New District, having a strong influence in the area mainly concentrated in the southeastern part. Many cold spots clustered in the central urban area to cool the thermal environment: the cooled area was 6.5 times larger than the area of intense cooling influence. Our study provides a method for identifying health risks in urban spaces, lays a theoretical foundation to improve the planning of urban green space systems, and offers some decision-making guidance for the planning of healthy cities.